Kecombrang (Etlingera elatior), a revivingly popular Indonesian culinary herb - Indro Prastowo; Mustofa Ahda; Nani Aprilia; Risanti Dhaniaputri (Journal of Ethnic Foods)
Abstract Kecombrang (Etlingera elatior) has long been utilized in Indonesian cuisine due to its unique flavors and aromas, enhancing the freshness and maintaining the sensory characteristics of foods since the ancient time. This study is a literature review exploring the diversity of Indonesian Kecombrang-based foods which are rarely reported. Other perspectives (botanical, chemical, gastronomical, historical, cultural and educational aspects) give the supporting views that could strengthen and enrich the meaning of the diversity. The data were obtained from online and offline literatures, which were subsequently tabulated prior to be written as a manuscript. Kecombrang is featured in more than 80 Indonesian traditional dishes such as Gurame Kincung, Pindang Ikan Bunga Kecombrang, Sambal Honje and Pecel Kecombrang. The chemical constituents like ascorbic acid, citric acid, fructose, myrcene, α-pinene, β-pinene, limonene, 3-O-caffeoylquinic acid and 5-O-caffeoylquinic acid contribute to the herb’s sour, slightly sweet, slightly bitter, slightly pungent and astringent flavors and fruity, earthy, slightly pungent, pine-like and lemon-like aromas. The herb also demonstrates several medical advantages such as anti-microbial, anti-oxidant, anti-tumor, anti-hyperglycemic, anti-hyperuricemic, anti-obesity and anti-inflammatory activities. Unfortunately, the herb’s popularity waned during certain periods of Indonesian history due to modernization. However, a renewed awareness on the healthy living and the growth of the Indonesian hospitality industry—especially following the COVID-19 pandemic—has sparked a revival of interest in Kecombrang, inspiring contemporary fusion dishes such as Kecombrang ice cream and pizza Kecombrang. Furthermore, the conservation of Kecombrang’s gastronomical values can be obtained through education, ensuring these traditions are passed on to the next generation (millennials and Gen-Z).